PEMBERDAYAAN KADER KESEHATAN DALAM DETEKSI DINI DIABETES MELLITUS DENGAN MENGGUNAKAN SUGAR HUNT - Ramadhani, Dwi Yuniar; Kurniawan, Afif; Hardiyanti, Siti (PPM STIKES Adi Husada, 2025)
Introduction & Aim: Health cadres are a form of active participation in society, equipped with knowledge and skills. Health cadres are not just extension agents but also liaisons with health centers and the early detection of health problems. Early detection of health problems is an anticipation for a person to become aware of their condition. Health problems such as diabetes mellitus can be anticipated by detecting lifestyles that are at risk of diabetes mellitus. This community service aims to increase knowledge, conduct random blood glucose checks, and identify lifestyles at risk of developing diabetes mellitus. Method of Activity: are health counseling, blood glucose checks, and detection of lifestyles at risk of diabetes mellitus using Sugar Hunt. Results: of community service activities were obtained by 29 people (85%) with a good level of knowledge and most of them were not at risk of diabetes mellitus, as many as 18 people (53%) and the results of random blood glucose tests showed normal as many as 18 people (53%). Discussion: Health education activities with interesting media will make it easier for the audience to remember and apply and carry out early detection as an anticipatory step. If you already have diabetes mellitus, it is essential to perform regular blood glucose checks at your nearest health service.